A cloud detection neural network for above-aircraft clouds using airborne cameras - Nied, Joseph; Jones, Michael; Seaman, Shane; Shingler, Taylor; Hair, Johnathan; Cairns, Brian; Gilst, David Van; Bucholtz, Anthony; Schmidt, Sebastian; Chellappan, Seethala; Zuidema, Paquita; Van Diedenhoven, Bastiaan; et al. (Frontiers in Remote Sensing, 2023)
For aerosol, cloud, land and ocean remote sensing, the development of accurate cloud detection methods, or cloud masks, is extremely important. For airborne passive remote sensing, it is also important to identify when clouds are above the aircraft since their presence contaminates the measurements of nadir-viewing passive sensors. We describe the development of a camera-based approach to detecting clouds above the aircraft via a convolutional neural network called the Cloud Detection Neural Network (CDNN). The CDNN enables cost-effective detection of clouds above the aircraft using an inexpensive camera installed in the cockpit for airborne science research flights where there are no dedicated upward-looking instruments for cloud detection, the installation of which requires time-consuming and expensive aircraft modifications, in addition to added mission cost and complexity of operating additional instruments. We quantify the performance of this CDNN using human-labeled validation data where we report a 96% accuracy in detecting clouds in testing datasets for both Zenith-viewing and Forward-viewing models. We assess our performance by comparing the flight-averaged cloud fraction of zenith and forward CDNN retrievals with that of the prototype hyperspectral total-diffuse Sunshine Pyranometer (SPN-S) instrument’s cloud optical depth data. Comparison of the CDNN with the SPN-S on time-specific intervals resulted in 93% accuracy for the zenith-viewing CDNN and 84% for the forward-viewing CDNN. The comparison of the CDNNs with the SPN-S on flight-averaged cloud fraction resulted in an agreement of 0.15 for the Forward CDNN and 0.07 for the Zenith CDNN. We quantify the ability of the CDNN to identify the presence of clouds above the aircraft using a forward-looking camera mounted inside the aircraft cockpit compared to the use of an All-Sky upward-looking camera that is mounted outside the fuselage on top of the aircraft. We present results from the CDNN based on airborne imagery from the NASA Aerosol Cloud Meteorology Interactions Over the Western Atlantic Experiment (ACTIVATE) and the Clouds, Aerosol and Monsoon Processes-Philippines Experiment (CAMP2Ex). For CAMP2Ex 53% of flight dates had above-aircraft cloud fraction above 50%, while for ACTIVATE 52% and 54% of flight dates observed above-aircraft cloud fraction above 50% for 2020 and 2021, respectively.